An exploratory study of expectations of adolescents from parents and siblings - Bautista, Ma. Joanna A.; Mamauag, Charmaine Grace P.; Macan, April Umali (2009.)
This study explores the expectations of adolescents from their parents and siblings. Thirty adolescents ages 17 to 18, from the University of the Philippines, Diliman wrote their expectations from their parents and siblings inside a human illustration and participated in a follow-up interview. Descriptive statistics were used to analyze data and t-test to show comparison between male and female respondents. Findings show that most of the adolescents' expectations from parents and siblings fall under care and protection followed by socialization, economic, and spiritual. There is no significant difference between the expectations of male and female respondents from their parents and siblings. The adolescents are generally satisfied on how their parents ans siblings meet their expectations.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Parent and child -- Philippines; Teenagers